Efektivitas Program Kelas Merdeka Komunitas Save Street Child Terhadap Perkembangan Proses Interaksi Anak Jalanan - Prastya, Eka Novan Rizky (Jurnal Dialektika Pendidikan IPS, 2022)
The problem of street children is a complex problem in Indonesia. Street children often associated with various kinds of criminal acts such brawls, drug abuse, and not even a few street children are victims of exploitation to sexual violence. This research uses a method with a qualitative type of approach, this approach has a procedure in producing descriptive data as a complex picture according to the reality that occurs. The subjects in this study were street children and the Save Street Child Sidoarjo Community. The purpose of this study is to (1) Find out the role of the Save Street Child Sidoarjo community in improving the quality of education for street children (2) Knowing the development in street children after joining the Save Street Child Sidoarjo Community (3) Describing the effectiveness of the independent class program on the development of the interaction process of street children. The results of the study concluded that the life patterns of street children are not in accordance with their growth and development processes, thus giving rise to deviations in life patterns in the process of social interaction of children, it is proven that many of the street children cannot have a good interaction relationship due to accepted social discrimination. Based on these problems, the Save Street Child Sidoarjo Community provides empowerment classes by applying a Street-based and Centre-based approach system which is expected that the holding of empowerment classes can provide improvement in street children both from cognitive, affective, and psychomotor aspects